Rules and Policies Related with Good Governance When Corona Virus 2019 (COVID19) Pandemic - Solechan Solechan (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2020)
The policy made by the government in relation to COVID 19, became a quite heated discussion among the community. In fact, many observers are questioning the policy. At present, the government is faced with two choices, namely maintaining the lives of citizens or maintaining the economy. Policies taken by the government must be based on the principle of good governance. The principle of good governance is an important principle in making policy. One of the principles in good governance is the principle of community participation. Through this research, we will see how community participation is related to policies made by the government, moreover, public awareness is still lacking related to government policies to deal with this pandemic. Keywords: Government, principle, community participation Abstrak Kebijakan yang dibuat oleh pemerintah terkait dengan COVID 19, menjadi pembahasan yang cukup hangat dikalangan masyarakat. Bahkan, para pengamat banyak yang mempersoalkan kebijakan tersebut. Saat ini, pemerintah dihadapkan dengan dua pilihan, yaitu mempertahankan nyawa warga negara atau mempertahankan perekonomian. Kebijakan yang diambil oleh pemerintah, harus didasari oleh prinsip good governance. Prinsip good governance ini menjadi prinsip yang penting dalam mengambil kebijakan. Salah satu prinsip yang ada di good governance adalah prinsip partisipasi masyarakat. Melalui penelitian ini, kita akan melihat bagaimana partisipasi masyarakat terkait kebijakan yang dibuat oleh pemerintah, terlebih lagi, kesadaran masyarakat yang masih kurang terkait dengan kebijakan pemerintah untuk menangani pandemi ini. Keywords: Pemerintah, Prinsip, Partisipasi Masyarakat